Pengaruh Dimensi Kualitas Layanan Kesehatan terhadap Kepuasan Pasien Askes PNS Rawat Inap Rumah Sakit Anutapura Palu - Hafied, Hamzah (Universitas Brawijaya, Indonesia, 2011)
The purpose of this study were to: 1) understand and analyze the influence of health service quality dimensions are: tangibility, reliability, responsiveness, assurance and emphaty significant effect on patient satisfaction Askes civil servants in the Hospital inpatient Anutapura Palu, and 2) to know and to analyze variable The most dominant influence on patient satisfaction Askes civil servants in the Hospital inpatient Anutapura Palu. The study population was all patients Askes civil servants in the inpatient hospital Anutapura in Palu. The sampling method purposive sampling. Method of data analysis using descriptive statistical analysis, and multiple regression analysis. The results showed that both variables simultaneously and partially tangibility, reliability, responsiveness, and empathy significantly influence patient satisfaction Askes PNS Hospital inpatient Anutapura Palu, while no significant assurance variables. Of the four independent variables that influence that is used in determining the level of patient satisfaction with inpatient PNS Askes, it turns out tangibility variable has a dominant influence in improving patient satisfaction Askes civil servants in the Hospital inpatient Anutapura Palu.